IMPROVING LEARNING MATHEMATICS ACTIVITY WITH THE THINK PAIR SHARE LEARNING MODEL - Nafida Hetty Marhaeni; Nuryadi Nuryadi (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Students are required to be actively involved during the learning process in accordance with the development of 21st-century learning. Student learning activities can occur through expressing opinions, solving problems, and discussing materials during the learning process. Learning models should always implement the stimulation of these abilities. Thus, this study is to analyze the influence of the Think Pair Share learning model on students' learning activities. This study was an experimental study with a pretest-posttest control group design. The population in this study was all class 8 as many as 192 students in one of the junior high schools in Yogyakarta, Indonesia. Students belonging to class VIIIA (32 students) were the experimental students' group, and students in VIIIC (32 students) were the control group. Data was collected based on 15 items of students’ activeness in learning mathematics. The results demonstrated that the application of the Think Pair Share learning model had an impact on the activeness of student learning. In addition, Think Pair method can improve the activeness of learning mathematics students, higher than in classes that implemented conventional learning models (25.31 > 15.78). This is because the application of the Think Pair share learning model provides opportunities for students to think, respond, and present problems provided by teachers so that students are fully involved during the mathematics learning process. The recommendations for further research can be carried out in several schools not just one school, student learning activity can also be increased by using other cooperative models, and can be further improved whether there are other competences that can boost the model's usage.